Sarcasm in Nadine Courtney's All-American Muslim Girl - Salsabila, Khirza; Djohar, Hasnul Insani (Faculty of Humanities, Diponegoro University, 2023)
This research examines how prejudice appears in Nadine Courtney’s All American Muslim Girl (2019) and investigates how the novel uses sarcasm to resist prejudice. This research engages with Elisabeth Camp's sarcasm theory and Gordon Willard Allport's concept of prejudice. Employing a qualitative research methodology, the research utilizes close textual analysis to dissect dialogues among characters as the primary data source. Based on the research findings, this research identifies two levels of prejudice within the novel All American Muslim Girl. The findings show that sarcasm is a useful technique for expressing opposition and resisting prejudice. By using biting and sarcastic words, it can effectively counter prejudice and stereotypes. In conclusion, through biting and satirical language, the characters adeptly contradicted stereotypes and resisted prejudice, emphasizing sarcasm's unique potential as an intelligent aesthetic and social strategy. This research underlines the importance of sarcasm in fostering insightful dialogue and promoting social change by countering prejudice in contemporary Muslimah or Muslim women’s literature.